02.46 Microrna-146a and disease activity in sle patients. (1st March 2017) - Shumnalieva, Russka; Kachakova, Darina; Monov, Simeon; Kaneva, Radka; Choumnalieva–Ivanova, Viara; Kolarov, Zlatimir; Rashkov, Rasho
Abstract : Background: Altered expression of microRNAs have been implicated in the pathogenesis of SLE due to their role in both the adaptive and innate immunity. Recent studies are trying to identify aberrant microRNA level as a diagnostic signature of SLE as well as to understand a role of specific microRNAs as biomarkers for disease activity (DA) and progression. The aim of our study was to evaluate the peripheral blood (PB) expression of microRNA-146a (miR-146a) in SLE patients and to determine its correlation with the DA in the clinical practice. Materials and methods: 40 SLE patients were included in the study. miR-146a expression levels in whole PB samples were determined by PCR (SYBR Green technology). 2 -ΔΔCt method was used for analysis. 32 healthy donors were used as controls. The DA was determined by DA index (SLEDAI) with 24 descriptors. SPSS v20 was used for ROC curve and Spearman correlation analysis. Results: miR-146a was overexpressed in 62.5% of the patients and none of the patients showed underexpression of miR-146a. ROC curve analysis showed that the expression levels of miR-146a (AUC-0.711, p=0.002) in PB could discriminate SLE patients from HCs with 82.5% sensitivity and 56.2% specificity. miR-146a showed statistically significant correlation with the diagnosis (rs 0.363) and age (rs 0.239) but there was no correlations with SLEDAI nor with the immunological activity according to ANA titer, a-dsDNA, a-Sm, a-b2GPI, a-CL antibodies, C3 and C4 complement levels. Conclusions: miR-146a is a known negative regulator of the type I interferon pathway by targeting the key signalling proteins and its underexpression may contribute to the disease activity of SLE as well as to the disease development. We didn't find a correlation between the levels of miR-146a and DA as a whole as well as with the immunological activity which might reflect the variants of SLE DA in the patients who participated in the study, the difference in their genetic background or in the used medications but larger study is needed to confirm these results in the clinical practice. Acknowledgement: The study was supported by Grant 53/2014 funded by Medical University – Sofia, Bulgaria.